2005
DOI: 10.1088/0953-8984/17/35/009
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy, disorder, and superconductivity in CeCu2Si2under high pressure

Abstract: Abstract. Resistivity measurements were carried out up to 8 GPa on single crystal and polycrystalline samples of CeCu 2 Si 2 from differing sources in the homogeneity range. The anisotropic response to current direction and small uniaxial stresses was explored, taking advantage of the quasi-hydrostatic environment of the Bridgman anvil cell. It was found that both the superconducting transition temperature T c and the normal state properties are very sensitive to uniaxial stress, which leads to a shift of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Moreover, at this V magnetic order is still present in CeAu 2 Si 2 but is absent in CeCu 2 Si 2 , which supports the idea that magnetic order and SC are not directly related [6]. For ρ 0 > 50 µΩcm, the depression of T bulk c of CeCu 2 Si 2 with increasing ρ 0 becomes much weaker, and SC survives even when ρ 0 is of the order of the Ioffe-Regel limit [34]. However, the large ρ 0 could be due to the effect of Kondo holes [35,36], and thus is no longer a good indication of the level of disorder.…”
Section: Comparison With the Results Of Ceau2si2(sn)supporting
confidence: 70%
“…Moreover, at this V magnetic order is still present in CeAu 2 Si 2 but is absent in CeCu 2 Si 2 , which supports the idea that magnetic order and SC are not directly related [6]. For ρ 0 > 50 µΩcm, the depression of T bulk c of CeCu 2 Si 2 with increasing ρ 0 becomes much weaker, and SC survives even when ρ 0 is of the order of the Ioffe-Regel limit [34]. However, the large ρ 0 could be due to the effect of Kondo holes [35,36], and thus is no longer a good indication of the level of disorder.…”
Section: Comparison With the Results Of Ceau2si2(sn)supporting
confidence: 70%
“…42 Around p V , the maximum T onset c and T ρ=0 c coincide. Above p V , in several samples 3,41,43 the superconducting region extends to high p; that is, the decrease of T onset c (p > p V ) is less steep than shown in Fig. 1, but may exhibit a jump close to 8 GPa.…”
Section: General Relevancy Of ρ( P) Analysismentioning
confidence: 82%
“…36) CeCu 2 Si 2 has been the subject of intensive study by the authors, in which we showed that the enhancement of T c under pressure was linked to a sharp Ce valence transition. 8,[37][38][39][40][41][42] The link between superconductivity and valence change had been noted by Jaccard and coworkers since the first measurements of CeCu 2 Si 2 under high pressure in 1984. 43) The isostructural sister compound CeCu 2 Ge 2 was shown to behave in a very similar way, with a shift of around 10 GPa corresponding to the larger atomic size of Ge.…”
Section: Cecu 2 Simentioning
confidence: 99%